An evaluation of hemp fiber for furnishing applications - De Miranda, DeeDee, author; Sarkar, Ajoy, advisor; Sparks, Diane, committee member; Most, David, committee member (Colorado State University. Libraries, 2011)
By all accounts, petroleum resources currently used as raw material for manufacturing synthetic fibers are rapidly depleting. It is urgent that professionals in the textile industry begin to consider alternative resources for raw material used for fiber. While contemplating replacement resources it is important that sustainable, renewable and less polluting natural fibers be considered for uses hitherto dominated by synthetic fibers. Among natural fibers, the bast fiber hemp is a potential substitute due to its excellent fiber properties. In addition to its desirable textile characteristics, hemp is often praised as an excellent rotational crop requiring little use of pesticides. Historically, hemp has been used for industrial purposes including ropes, nets, paper, cloth, sails, and oil. According to recent published reports, use of hemp fiber in the furnishings market is on the rise. However, no published research has evaluated the suitability of hemp for furnishing products. Therefore, the goal of this investigation was to shed light on the viability of hemp fiber for furnishing applications via studies designed to evaluate the performance of hemp fiber towards meeting ASTM specifications for woven upholstery fabrics. The primary objective of the study was to compare and contrast the performance characteristics of 100% woven cotton and 100% woven hemp fabrics of three different weave structures with regard to colorfastness to crocking, colorfastness to light, soil release, colorfastness to water, flammability, abrasion resistance, tearing strength, breaking strength and elongation. It was found that there was no difference between cotton and hemp fabrics in terms of colorfastness to crocking; oily stain release; flammability; tearing strength; breaking strength and elongation. For colorfastness to light, the hemp fabrics in this study exhibited noticeable color change. It is suggested that an ultraviolet absorber treatment may provide enhanced resistance to color change caused by exposure to light. With regard to colorfastness to water, hemp fabrics performed satisfactorily indicating that steam cleaning of hemp furnishing fabrics in this study is not a concern. For abrasion resistance, the performance of hemp fabrics was slightly less than the cotton fabrics in the study. In conclusion, based on test results and benchmark comparisons, this study indicates that hemp is a viable fiber for use in furnishing applications. However, due to the small sample size of the study, the results cannot be extrapolated to the population of all commercially available hemp and cotton fabrics.
Keywords: testing hemp; hemp furnishings; hemp upholstery; hemp performance; hemp; hemp comparisons